IMPACT OF EXCESSIVE GADGET USE AWARNESS EDUCATION ON ELEMENTARY STUDENTS LEARNING MOTIVATION - Siti Robiatus; Mery Angreani Safitri (Community Service Journal of Indonesia, 2026)
Excessive gadget use may negatively affect learning motivation and academic engagement among elementary school students. This study aimed to determine the effect of Excessive Gadget Use Awareness Education on students' learning motivation. This study aimed to evaluate the effectiveness of health education on the dangers of excessive gadget use in improving learning motivation among elementary school students. The intervention was conducted at SDIT Elhaq Sidoarjo, involving 64 respondents selected from a population of 87 students. A quasi-experimental design with a pre-test and post-test approach was employed using a researcher-developed Learning Motivation Questionnaire consisting of 20 items. The findings revealed that prior to the intervention, 62% of participants had limited understanding, while 38% demonstrated a moderate level of understanding. Following the intervention, 78% of participants showed improved understanding, whereas 22% continued to exhibit limited comprehension. The results indicate that health education significantly enhances students’ awareness of the negative impacts of excessive gadget use and fosters more positive attitudes toward learning. In conclusion, structured and age-appropriate educational interventions are effective strategies for promoting responsible gadget use and improving learning motivation among elementary school children. These findings highlight the importance of integrating digital health education into school-based programs to optimize students’ academic engagement and developmental outcomes.